Професійна підготовка бакалаврів гуманітарних наук у галузі журналістики в університетах США - Марціхів, Христина Романівна (Національний університет "Львівська політехніка", 2019)
У дисертаційній роботі запропоновано вирішення наукового завдання щодо виявлення особливостей професійної підготовки бакалаврів гуманітарних наук у галузі журналістики в університетах США: узгодження професійних та освітніх стандартів на федеральному та штатовому рівнях; збалансоване використання потенціалу аудиторної та самостійної роботи студентів; диверсифікація освітньо-професійних програм підготовки журналістів, ступенів та кваліфікацій; міждисциплінарний та інтегрований характер освітньо-професійних програм; широке використання методів активного навчання; активізація академічної мобільності здобувачів вищої освіти; систематичне забезпечення моніторингу якості освіти, що сформувалося під впливом міжнародного освітнього простору. Обґрунтовано професійну підготовку бакалаврів гуманітарних наук у галузі журналістики як науково-педагогічну проблему, в основу якої покладено теорії, концепції, принципи, підходи. Розкрито організаційно-педагогічні засади професійної підготовки бакалаврів гуманітарних наук у галузі журналістики. Здійснено порівняльно-педагогічний аналіз професійної підготовки бакалаврів у галузі журналістики в університетах США та України, виявлено спільні та відмінні риси в обох країнах. Окреслено можливості використання конструктивних ідей американського досвіду професійної підготовки бакалаврів гуманітарних наук у галузі журналістики в умовах університетської освіти України. Уточнено зміст та специфіку організації професійної підготовки бакалаврів гуманітарних наук у галузі журналістики. Подальшого розвитку набули положення про організацію професійної підготовки майбутніх фахівців у галузі журналістики на основі співпраці університетів з урядовими та неурядовими організаціями, місцевої громади та потенційними роботодавцями; про комплексне використання традиційних та інноваційних методів навчання, зокрема кейсів, польового методу навчання, практичного навчання у громаді. В диссертационной работе предложено решение научной задачи по выявлению особенностей профессиональной подготовки бакалавров гуманитарных наук в области журналистики в университетах США: согласование профессиональных и образовательных стандартов на федеральном и штатном уровнях; сбалансированное использование потенциала аудиторной и самостоятельной работы; диверсификация образовательно-профессиональных программ подготовки журналистов, ступеней и квалификаций; междисциплинарный и интегрированный характер образовательно-профессиональных программ; широкое использование методов активного обучения; активизация академической мобильности соискателей высшего образования; систематическое обеспечение мониторинга качества образования, сформировавшиеся под влиянием тенденций международного образовательного пространства. Обоснованно профессиональную подготовку бакалавров гуманитарных наук в области журналистики как научно-педагогическую проблему, в основу которой положен теории, концепции, принципы, подходы. Раскрыты организационно-педагогические основы профессиональной подготовки бакалавров гуманитарных наук в области журналистики. Осуществлен сравнительно-педагогический анализ профессиональной подготовки бакалавров в области журналистики в университетах США и Украины, выявлено общие и отличительные черты в опыте обеих странах. Определены возможности использования конструктивных идей американского опыта профессиональной подготовки бакалавров гуманитарных наук в области журналистики в условиях университетского образования Украины. Уточнено содержание и специфику организации профессиональной подготовки бакалавров гуманитарных наук в области журналистики. Дальнейшее развитие получили положения об организации профессиональной подготовки будущих специалистов в области журналистики на основе сотрудничества университетов с правительственными и неправительственными организациями, местной общины и потенциальными работодателями; о комплексном использовании традиционных и инновационных методов обучения, в частности кейсов, полевого метода обучения, практического обучения в обществе. The thesis presents the solution to the research problem of identifying specificity of professional training of Bachelors of Arts in Journalism at the US universities (harmonization of professional and educational standards at the federal and state levels; balanced use of the potential of classroom and independent student work; diversification of educational and professional journalism training programs; the interdisciplinary and integrated nature of educational programs, degrees and qualifications; extensive use of active learning methods; activation of student academic mobility; systematic higher education quality assurance) that have been formed under the influence of tendencies of international educational space. Professional training of Bachelor of Arts in Journalism has been justified as a scientific and pedagogical problem, solving of which is based on theories, concepts, principles, approaches. On the basis of comparative and pedagogical analysis of professional training of Bachelor of Arts in Journalism at the universities of the USA and Ukraine common (systematic review and improvement of educational and professional programs for the training of future specialists in journalism, taking into account trends of the international and educational space, national educational traditions of the labour market and employers’ requirements; humanitarian and competence-oriented educational and professional programs covering compulsory and optional disciplines; credit-modular system; levels and degrees of higher professional education; implementation of training standards; conceptual and pedagogical fundamentals of professional training of journalists), distinctive (specific attributes of the US experience are: high level of integration into international space, autonomy of university system, flexibility of educational and professional programs; freedom of choice that allows students to form their own educational trajectory; diversification of educational and professional programs, degrees; interdisciplinary of programs; allocation of a considerable amount of student’s academic load to independent work; motivation to analytical research work, high level of academic mobility; volunteer and community activities of future media specialists; applying active methods of teaching; active use of information technologies; implementation of student-centred approach; collaboration of universities with potential employers with the aim of providing work for graduates and implementing joint projects; specific attributes of Ukraine’s experience are: low degree of integration into international educational space; theoretically oriented educational and professional programs, insufficient level of formation and development of practical skills; low level of right to choose optional disciplines and formation of an individual educational trajectory; philologically oriented curricula; allocation of a considerable amount of student’s academic load to classroom work; low level of student involvement into scientific and analytical research; the initial stage of intensification international academic mobility and the lack of internal academic mobility; the initial stage of establishing cooperation with domestic and foreign media organizations for students’ internship; setting up and improvement of media laboratories and centres for practical training of future journalists) features of the researched countries have been identified; recommendations on the use of constructive ideas of experience of professional training of Bachelors of Arts in Journalism at Ukrainian universities have been developed. The content and specifics of the professional training organization of Bachelors of Arts in Journalism have been clarified. The ideas of organization of professional training of journalists based on the collaboration of universities with governmental and non-governmental organizations, the local community and potential employers, comprehensive use of traditional and innovative teaching methods, in particular, case study, “field training method”, service learning have gained further development.
Профессиональная подготовка бакалавров гуманитарных наук в области журналистики в университетах США
Professional training of bachelors of arts in journalism at the US universities
Keywords: бакалавр гуманітарних наук; журналістика; професійна підготовка; освітньо-професійна програма; США; університет; бакалавр гуманитарных наук; журналистика; профессиональная подготовка; образовательно-профессиональная программа; США; університет; Bachelor of Arts; educational and professional program; journalism; professional training; USA; university; 378.4:73(043.5)